THE TRAINING AND DEVELOPMENT OF DIDACTIC COMMUNICATION COMPETENCIES IN AND THROUGH A VIRTUAL ENVIRONMENT - Florentin Remus MOGONEA (Universitaria Publishing House, Craiova, 2023)
The purpose of this study consists in the (partial) inventory of the digital competencies that general education teachers must have. Digital competencies represent integrated systems of knowledge, abilities, skills, attitudes and values, formed and developed through learning, which an individual has and which can be mobilized to solve various problems that arise in the process of collecting, storing, processing and disseminating information through information and communication technologies. In the 21st century, teachers must have digital competencies in order to face the challenges of the information age. The need to have a certain level of digital skills has two facets for teachers: an integrating part of professional competencies; incentive and catalyst for the development of students' digital skills, as a prerogative for their employment in the field of work. The areas of competency were determined in accordance with a set of national and international documents, belonging to the field of transversal digital key competencies from the framework document of the European Parliament and the European Council of 18th December 2006, regarding the key competencies for lifelong learning. From the wide spectrum of digital competencies, the ones selected and included in this document were those that were strictly necessary for a teacher to carry out professional activities with.